1995
DOI: 10.1097/00000542-199502000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Safety Assessment of Intrathecal Neostigmine Methylsulfate in Humans 

Abstract: The incidence and severity of these adverse events from intrathecal neostigmine appears to be affected by dose, method of administration, and baricity of solution. These effects in humans are consistent with studies in animals. Because no unexpected or dangerous side effects occurred, cautious examination of intrathecal neostigmine alone and in combination with other agents for analgesia is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
191
3
9

Year Published

1996
1996
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(216 citation statements)
references
References 24 publications
13
191
3
9
Order By: Relevance
“…Mean oxygen saturation (SpO 2 ) and respiratory rate were comparable between the three groups and other similar studies 8,10 with no patient developing hypoxemia (SpO 2 < 90%).There is no reported evidence of respiratory depression with the use of intrathecal neostigmine.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Mean oxygen saturation (SpO 2 ) and respiratory rate were comparable between the three groups and other similar studies 8,10 with no patient developing hypoxemia (SpO 2 < 90%).There is no reported evidence of respiratory depression with the use of intrathecal neostigmine.…”
Section: Discussionsupporting
confidence: 56%
“…None of the patients developed symptomatic bradycardia (<50 bpm) or hypotension defined as a decrease in mean arterial blood pressure by ≥ 20%. Lauretti et al 9 showed similar observations but our study was in contrast to Hood et al 8 who showed that spinally administered cholinergic agonist or cholinesterase inhibitors increase blood pressure and heart rate. The small dose (50-150 µg of neostigmine) could explain the lack of cardiovascular stimulation seen in our study.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…It has long been known that the direct and indirect activation of the cholinergic system produces analgesia in both animals (1,2,9,(16)(17)(18)21,23,24) and humans (20). Because sumatriptan is endowed with cholinergic antinociceptive properties and 8-OH-DPAT enhances ACh release, the goals of the present study were to explore whether other 5-HT 1A agonists, such as gepirone and 8-OH-DPAT, were able to increase the pain threshold in mice and then investigate whether a cholinergic mechanism underlies 5-HT 1A antinociception.…”
mentioning
confidence: 99%
“…The acetyl-choline esterase inhibitor neostigmine, has demonstrated a dose-dependant analgesia following spinal or epidural administration [11,12]. However, this central delivery of neostigmine is limited by dose-related side effects such as nausea, vomiting, pruritis, caused by cephalad spread of neostigmine in the cerebrospinal fluid [13,14].…”
Section: Introductionmentioning
confidence: 99%